ASSESSMENT OF GENETIC PARAMETERS OF BREAD WHEAT (Triticum aestivum L.) HYBRIDS UNDER SPEED BREEDING CONDITIONS - Levent YORULMAZ; Cuma AKINCI (Journal of Animal and Plant Sciences, 2026)
As an increasing world population and changing environmental conditions constrain food security, it is inevitable that the current rate of development of many strategic crops will be insufficient to meet future food demand. Depending on the generation time of plants, this rate of development varies. This study was carried out in speed breeding system greenhouses of Dicle University, Turkey in 2023-2024. In the study, genetic parameters and heterosis effects of F1 bread wheat hybrids (Triticum aestivum L.) developed under speed breeding conditions were investigated. Agronomic, physiological, and yield-related traits were evaluated using three bread wheat cultivars (Adana-99, Alada, and Lucilla) and their F1 hybrids, arranged in a completely randomized design (CRD). In study, heterosis over mid-parent and better-parent, potence ratio, genotypic and phenotypic variance, heritability and genetic advance based on days to heading, days to anthesis, heading time SPAD value, anthesis time SPAD value, plant height, spike length, number of grains per spike, grain weight per spike and total grain weight per plant were analyzed. The results revealed significant genetic variability among the hybrids, with the Alada × Adana-99 (P2 × P1) hybrid showing the highest gains in yield related traits such as total grain weight per plant and grain weight per spike. Especially, broad sense heritability (H2) and genetic advance (GA) values were high for days to heading (H2:0.87 and GA:5.16) and number of grains per spike (H2:0.66 and GA:5.32). High broad sense heritability and genetic advance values for these traits further confirm their relevance in breeding programs aimed at improving wheat productivity and resistance under speed breeding conditions. These findings highlight the usefulness of heterosis breeding and genetic parameter assessment in developing high-yielding and stress-tolerant wheat varieties.
Keywords: Wheat; speed breeding; hybrid breeding; heritability; genetic advance